2017
DOI: 10.1186/s12872-017-0564-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of myocardial involvement in acute myopericarditis in young adults

Abstract: BackgroundMyocardial involvement in young adults has various causes. Acute myopericarditis is one of the myocardial involvements in young adults. It is easy to confuse with acute ST-elevation myocardial infarction because of the electrocardiographic features. This study aims to investigate a number of imaging techniques and clinical features for acute myopericarditis in young adults (<30 years of age).MethodsThis retrospective study included 147 patients selected from the 2147 patients at the age of <30 with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
0
19
1
2
Order By: Relevance
“…Focal echobright is defined as local enhancement of echogenicity seen on 2‐dimensional echocardiography. It has been reported to be a distinctive feature only for the acute phase of myocarditis 1 . Indeed, at the 6‐month follow‐up, we did not see this phenomenon anymore.…”
Section: Introductioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Focal echobright is defined as local enhancement of echogenicity seen on 2‐dimensional echocardiography. It has been reported to be a distinctive feature only for the acute phase of myocarditis 1 . Indeed, at the 6‐month follow‐up, we did not see this phenomenon anymore.…”
Section: Introductioncontrasting
confidence: 61%
“…It has been reported to be a distinctive feature only for the acute phase of myocarditis. 1 Indeed, at the 6-month follow-up, we did not see this phenomenon anymore. Furthermore, we found that the detection of a reduced GLS value, regional disturbances of segmental myocardial strain, and diminished values of both GLS and GCS in the epicardial layer could help to diagnose myocarditis.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…14 Echocardiographic involvement was accepted as pericardial effusion or focal perimyocardial echo bright appearance. 15…”
mentioning
confidence: 99%
“…It is likely that the typical clinical presentations of myocardial infarction, such as chest pain, ST-segment elevation and incremental serum markers, appear in patients diagnosed with myocarditis [11]. In one study of clinically suspected cases, about a quarter of patients had reduced LVEF, sustained ventricular arrhythmias or symptoms of low cardiac output [12]. When the pericardium is involved, as in myopericarditis, chest pain with features similar to pericarditis will arise.…”
Section: Introductionmentioning
confidence: 99%